Optimization Study of the Ratio of Bioethanol Bioaceton Ron 90 on the Power and Emissions of a 110cc Gasoline Motor - Syva Kurniawan; Dwi Pebrianti (CV. Creative Tugu Pena, 2023)
Fossil fuels have become one of the main causes of increasing pollution in the world, especially in Indonesia. Comparisons between proposed bio-acetone fuel blends and other biofuels were introduced in a unique study. bio-acetone is a promising alternative and can improve performance and emissions over the others. The aim of the research was to determine the optimization of the ratio of bioethanol, bioacetone-Ron 90 to power and exhaust emissions (HC and CO). Fuel mixture ratio bioethanol, bioacetone - RON 90 ((3:7:10), (5:5:10), (7:3:10), (10:5:5), (7,5:7, 5:5), (5:10:5), (2,5:2,5:15), (3,5:1,5:15), (1,5:3,5:15)) and engine speed (2000, 3000, 4000, 5000, 6000) 110cc gasoline engine rpm. The data processing method uses the Response surface method. The results of research on power and emission tests that have been optimized, the optimum value for fuel ratio power at standard spark plugs, at a ratio of 1.5:3,5:15 and Rpm 4424.24 with a power of 8.02065 HP. The optimum value for HC emissions is at a ratio of 3:7:10 at Rpm 4222.22 and HC gas emissions are 43.9879 ppm. Optimum value for CO emissions at a ratio of 7.5:7.5:5 and 2000 rpm with a CO emission of 0.208712%. Keywords: Optimization Bioethanol, Biocetone, Power and Emissions